Evolution of the Geometric Structure of X39Cr13 Steel upon Thermochemical Treatment Specific to Medical-Grade Steels - Gwoździk, Monika; Bramowicz, Mirosław; Kulesza, Sławomir (Lubricants, 2022)
This paper presents the results of the multi-aspect surface characterization of X39Cr13 steel samples subjected to technological processes specific to medical instrumentation, such as heat and thermochemical treatment, as well as sterilization, which are implemented in corrosion resistance measurements. The application of numerical methods of fractal analysis to averaged profiles obtained from SEM images resulted in double-log plots of structure function, from which the determination of the fractal parameters of interest was possible. The discussion was focused on the fractal dimension D, which governs relative height variations upon scaling in length, and corner frequency fc, which separates the scaling behavior of different-order structures (particles and their aggregates). The obtained results show that the heat treatment leaves behind a granular structure of steel (D2 = 2.43; fc2 = 1.97 nm), whereas corrosion tests reveal the appearance of pits (D1 = 2.17; fc1 = 0.303 nm; D2 = 2.59; fc2 = 4.76 nm). In turn, the ion nitriding improves the resistance of steel X39Cr13 to local corrosion. The fractal analysis also shows that the structure of the nitrided layer differs insignificantly from that of the untreated material, seen only as a shortening of the radius of the self-similarity area by a factor of two (fc2 = 1 nm).